Technology-assisted cognitive-behavioral therapy intervention for end-stage renal disease. Issue 3 (27th May 2019) - Jakubowski, Karen P; Jhamb, Manisha; Yabes, Jonathan; Gujral, Swathi; Oberlin, Lauren E; Bender, Filitsa H; Steel, Jennifer L
Abstract: Technology-assisted cognitive-behavioral therapy (CBT) interventions have been conducted for symptoms including depression, pain, and fatigue in patients with chronic illnesses but not in end-stage renal disease (ESRD). The purpose of this study was to pilot the feasibility and acceptability of a technology-assisted CBT intervention in ESRD patients on hemodialysis (HD), share design and implementation lessons learned, and provide preliminary results on changes in select patient-reported symptoms. This was a single-center pilot feasibility study of adult ESRD patients on HD. Study eligibility required clinically elevated levels of at least one symptom (depression, pain, or fatigue). Patients met weekly with a CBT therapist for eight sessions, each 45–60 min, during HD sessions via a video-conferencing platform. Symptom questionnaires were completed at baseline and 3 months follow-up. Of 10 patients screened, 100% screened positive for at least one symptom, 100% of eligible patients consented, and eight (of 10) completed the intervention (mean age 59 years, 50% male, 50% African American). Patient adherence and satisfaction was high, and seven of the eight patients completed all eight prescribed sessions. Minimal interference with HD was reported. Preliminary results indicate no statistically significant changes in depression, fatigue, or pain at follow-up. However, there was small improvement in SF-36 Physical Component score [ t (7) = −2.60, p = .035], and four of the six patients (67%) with clinically elevated pain at baseline reported improvement at follow-up. A technology-assisted CBT intervention for ESRD patients was feasible, well-accepted, and required minimal additional resources in the HD setting. Larger, adequately powered clinical trials are needed to evaluate the effect on ESRD patient-reported outcomes.